Strength and Permeability of Cultivated Histosols Characterized by Differing Degrees of Decomposition - Dessureault-Rompré, J. (2020)
The objective of this study was to characterize the soil penetration resistance and the saturated hydraulic conductivity (ksat) in cultivated organic soils that differed in their degree of decomposition. Three fields in the plain of Montreal, in southwestern Quebec, were selected to provide a gradient of degrees of decomposition. Site 1 was classified as a Limnic Fibrisol, Site 2 was classified as a Terric Mesic Humisol, and Site 3 was classified as a Terric Humisol. At each site, penetration resistance and ksat were measured directly in the field. Penetration resistance, particularly at the 25‐cm depth and deeper, was found to increase with increasing soil degradation. An inverse relationship was observed for ksat in the compact layer. The results presented in this study indicate that penetration resistance and ksat are both linked to the degree of soil decomposition. However, the relationship between both parameters is complex, and both parameters are to be measured to achieve a more accurate characterization of organic soils. Further work could assess the depth of the compact layer, as well as the degree of decomposition of organic soils at different spatial scales using penetration resistance. In Histosols, accurately mapping ksat would help in designing field drainage system, as this soil property is difficult to predict from other parameters.